Creditless Recoveries - Abiad, Abdul (IMF Working Papers; Working Paper, 2011)
Recoveries that occur in the absence of credit growth are often dubbed miracles and named after mythical creatures. Yet these are not rare animals, and are not always miracles. About one out of five recoveries is "creditless", and average growth during these episodes is about a third lower than during "normal" recoveries. Aggregate and sectoral data suggest that impaired financial intermediation is the culprit. Creditless recoveries are more common after banking crises and credit booms. Furthermore, sectors more dependent on external finance grow relatively less and more financially dependent activities (such as investment) are curtailed more during creditless recoveries.